Transcriptomics of an extended phenotype: parasite manipulation of wasp social behaviour shifts expression of caste-related genes. Issue 1852 (12th April 2017) - Geffre, Amy C.; Liu, Ruolin; Manfredini, Fabio; Beani, Laura; Kathirithamby, Jeyaraney; Grozinger, Christina M.; Toth, Amy L.
Abstract : Parasites can manipulate host behaviour to increase their own transmission and fitness, but the genomic mechanisms by which parasites manipulate hosts are not well understood. We investigated the relationship between the social paper wasp, Polistes dominula, and its parasite, Xenos vesparum (Insecta: Strepsiptera), to understand the effects of an obligate endoparasitoid on its host's brain transcriptome. Previous research suggests that X. vesparum shifts aspects of host social caste-related behaviour and physiology in ways that benefit the parasitoid. We hypothesized that X. vesparum -infested (stylopized) females would show a shift in caste-related brain gene expression. Specifically, we predicted that stylopized females, who would normally be workers, would show gene expression patterns resembling pre-overwintering queens (gynes), reflecting gyne-like changes in behaviour. We used RNA-sequencing data to characterize patterns of brain gene expression in stylopized females and compared these with those of unstylopized workers and gynes. In support of our hypothesis, we found that stylopized females, despite sharing numerous physiological and life-history characteristics with members of the worker caste, show gyne-shifted brain expression patterns. These data suggest that the parasitoid affects its host by exploiting phenotypic plasticity related to social caste, thus shifting naturally occurring social behaviour in a way that is beneficial to the parasitoid.